The immunological challenges of malaria vaccine development - Jiraprapa Wipasa (2018)
Malaria remains an important public health problem throughout the tropical world causing immense human suffering and impeding economic development. Despite extensive research for > 100 years, options for preventing malaria remain limited to vector control and chemoprophylaxis. The complexity of the organism and its life cycle have, thus far, thwarted vaccine development and exacerbated the perennial problems of drug resistance. Nevertheless, development of a vaccine against malaria that reduces morbidity and mortality, and ideally also reduces transmission, has long been seen as an essential component of a sustainable malaria control strategy. In this article the authors review the biological challenges of malaria vaccine development, summarise some of the recent advances and offer some immunological insights which might facilitate further research. © 2007 Informa UK Ltd.